2015
DOI: 10.1515/biolog-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of Hemolivia mauritanica (Apicomplexa: Haemogregarinidae) and its vector Hyalomma aegyptium in tortoises of Iran

Abstract: Distribution pattern, prevalence and intensity of parasitaemia of heteroxenous apicomplexan blood parasite Hemolivia mauritanica and its vector tick Hyalomma aegyptium have been studied in 264 tortoises (212 Testudo graeca and 52 T. horsfieldii) throughout the Iranian territory. In T. graeca the highest prevalence and intensity of parasitaemia for H. mauritanica were recorded in the temperate mid and northern parts of the Iranian plateau, while the lowest values were found in the arid central part of Iran. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Hemolivia mauritanica is a pathogen of tortoises and has H. aegyptium as the definitive host [ 11 ]. The results obtained in this study are in accordance with previous prevalence levels from Lebanon (38%), Algeria (30.4%) and Bulgaria (14%), but are much lower when compared with results observed in Turkey (82%), Romania (84%), Syria (82%) and Greece (81%) [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Hemolivia mauritanica is a pathogen of tortoises and has H. aegyptium as the definitive host [ 11 ]. The results obtained in this study are in accordance with previous prevalence levels from Lebanon (38%), Algeria (30.4%) and Bulgaria (14%), but are much lower when compared with results observed in Turkey (82%), Romania (84%), Syria (82%) and Greece (81%) [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite the high variation in environmental factors among the studied localities, no significant relationships were observed between the climatic parameters investigated, and infestation intensity and prevalence, respectively. Previous studies have shown that low humidity may be a key factor limiting H. aegyptium distribution (Široký et al ., ; Javanbakht et al ., ). However, the present study found a significant and positive relationship between the intensity of tick infestation and the density of the tortoise population, indicating that ticks tend to concentrate their questing efforts wherever their food (hosts) is most abundant (Godfrey et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The detected mean intensity of infestation (9.4) at Djelfa is among the highest yet encountered among T. graeca , whereas intensities at the remaining three studied localities (1.7–5.9) were comparable with available data from Jordan [0.2–5.9 (Petney & Al‐Yaman, )], Russia [5.2 (Robbins et al ., )], the Balkans [1.3 (Široký et al ., )], Italy [3.9 on tortoises imported from North Africa (Brianti et al ., )] and Tunisia [4.3 (Gharbi et al ., )]. To date, the highest infestations among Testudo tortoises were recorded in some Iranian localities in T. graeca [locally up to 21.0 ± 8.1 (Javanbakht et al ., )] and in Greece in T. marginata [17.2 ± 7.7 adult H. aegyptium per tortoise (Široký et al ., )]. However, these data may be skewed by the small sample size at the Iranian localities or influenced by the relatively large size of the T. marginata host.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence is highly variable along its distribution range, although in general, values are higher in the eastern range decreasing toward the western and south (Široký et al., 2009). The highest prevalence has been reported in Romania (84%; Široký et al., 2009) and Iran (100%; Javanbakht et al., 2015). Regarding North Africa and Anatolia, prevalence reported include 51.9% in Turkey (Akveran et al., 2020) and between 6.25‐30.4% in Algeria (Široký et al., 2009; Tiar et al., 2010), while there are no positive reports in Morocco or Tunisia (Harris et al., 2013; Laghzaoui et al., 2020; Široký et al., 2009).…”
Section: Discussionmentioning
confidence: 97%